Surgical-orthodontic with atypical extraction pattern as a treatment for an anterior open bite: a case report - Alwadei, Abdurahman (Journal of the Pakistan Medical Association, 2023)
This case report described the surgical-orthodontic interdisciplinary treatment of a patient with skeletal anterior open bite, class III skeletal pattern, steep mandibular plane, increased lower face height, and thin mandibular symphysis. The orthodontic preparation included an unusual extraction pattern (maxillary right first molar, maxillary left second premolar, and mandibular right central incisor), combined with two-jaw surgery comprised of maxillary advancement and differential impaction, bilateral malarplasty augmentation and mandibular asymmetric bilateral sagittal split osteotomy setback. The follow-up of a rare complication of surgical hooks breakage during surgery is reported. Guided by 3-dimesional digital platforms, treatment planning and execution, resulted in a more balanced and proportionate face with functional occlusion, and the case stability is shown in a 32-month follow-up. Keywords: CL III malocclusion, (AOB) anterior open bite, dentofacial deformity, orthognathic surgery, digital dentistry.